Simple Additive Weighting (SAW) Method on The Selection of New Teacher Candidates at Integrated Islamic Elementary School - Rozi Meri (Sekolah Tinggi Ilmu Komputer (STIKOM) Tunas Bangsa, 2020)
A decision support system is a computer-based information system that produces various alternative decisions to assist management in dealing with various structured or unstructured problems using data or models, one of which is in the problem of recruiting new teachers so that decisions are made in the right direction. The research method used in this study is SAW (Simple Additive Weighting), which is one of the algorithms used for decision making. The SAW algorithm is also known as the weighted addition algorithm. This method requires a decision matrix normalization process (x) to a scale that can be compared with all available alternative ratings. The authors took a case study at SD IT Cinta Qur'an. SD IT Cinta Qur'an is one of the elementary schools managed by the As-Salam Ilal Jannah Foundation, which is located in Tanjung Balik Village, Solok Regency. The result of the calculation of the saw method is in the form of information that can be taken into consideration by the school in making decisions on new teacher selection. In this study, six candidates as samples with five criteria were used in the calculation of the SAW method to obtain the best candidate rankings to make decisions by ordering from maximum to minimum value. It can be concluded that the SAW method can be used to support decisions in the selection of new teacher candidates by building a decision support system modelling.